Audience response to travel photos and Arab destination image - Syed-Ahmad, S.F.; Musa, G.; Klobas, J.E.; Murphy, J. (Taylor & Francis, 2013)

(untitled)
This research note explores how members of Flickr, the world's most popular photo community, share and respond to travel photographs of Arab countries. As photo-sharing becomes commonplace, researchers could use audience responses to photos to examine destination image. This note also extends the offline Visitor Employed Photography technique online, by including shared photographs and audience response. We observe that the images conveyed in the online photos that generated most audience response differ from those in official travel and tourism documentation. This result benefits both destination image research and practice in the analysis of audience response to online travel photos.